ANALYSIS OF BATIK INDUSTRY AS A CENTER OF ECONOMIC DEVELOPMENT TOWARDS INTERNATIONAL LEVEL - Kaila Ismail; Mia Sulistianti; Nisrina Luthfiah; Rachma Ditia; Farahdinny Siswajanthy (Triwikrama: Jurnal Ilmu Sosial, 2025)
The Batik Industry in Indonesia is one of the textile and ready-made clothing industry commodities which is a heritage and a wealth of the Indonesian nation that characterizes the diversity of cultures in Indonesia. UNESCO recognized Indonesian batik in 2009 and since then batik in Indonesia has developed very rapidly in terms of fashion or mode used by the general public and indigenous peoples in Indonesia. The development of the batik industry in Indonesia still has obstacles where these obstacles are not far from batik printing technology. The purpose of this study is to analyze the batik industry in Indonesia, as well as what potentials Indonesia has so that it can improve this batik culture to the international level. If batik which is a cultural wealth in Indonesia can move internationally, then batik can be better known by foreign communities and even batik can become an iconic symbol of Indonesia internationally.